3D-printed HZSM-5 and 3D-HZM5@SAPO-34 structured monoliths with controlled acidity and porosity for conversion of methanol to dimethyl either. (15th November 2020) - Magzoub, Fatima; Li, Xin; Lawson, Shane; Rezaei, Fateme; Rownaghi, Ali A.
Highlights: Three-dimensional (3D) printing of HZSM-5 and HZSM-5@SAPO-34 structured monolith catalyst with hierarchical porosity. The mesoporosity and acid strength were tuned toward improved DME selectivity. The selectivity towards DME was increased and correlated to the presence of moderate Brønsted acidity. Abstract: The ability to control the morphology and porosity of zeolite-structured monolith is an important step in the design of zeolite-based catalysts. Herein, additive manufacturing method was used for the rapid synthesis of H-ZSM-5 structured monoliths (3D-HZSM5) with hierarchical porosity (macro- meso -micro) and controlled type and density of acid sites. After 3D-HZSM5 monolith formation, the silicoaluminophosphate (SAPO-34) was grown on the 3D-HZSM5 structured monolith surface via secondary growth method for formation of 3D-HZSM5@SAPO-34 structured monolith. The samples were characterized before and after SAPO-34 growth by XRD, N2 physorption, NH3 -TPD, Py-IR and SEM. The characterization results revealed formation of SAPO-34 layer on 3D-HZSM5 structured monolith and also modification also imply that formulation of H-ZSM-5 powder into monolith resulted in slightly less Brønsted acid sites while the density of Lewis acid sites increased. The performance of the 3D-HZSM5 and 3D-HZSM5@SAPO-34 structured monoliths were investigated in catalytic conversion of methanol to dimethyl ether (DME) over a temperature range of 180 to 320 °C for 10 h time on stream. The selectivity to DME was significantly increased as a result of modification in acidity and porosity of the 3D-printed HZSM-5 structured monolith as compared to its powder counterpart and also 3D-HZSM5@SAPO-34 structured monolith. SAPO-34 growth enhanced the density of strong acid sites which caused further conversion of DME to higher hydrocarbons. The highest DME selectivity reached 96% on 3D-HZSM5 structured monolith at 180 °C, which also achieved 70% conversion of methanol.